A Comparative Study of patients, Undergoing Transurethral Resection of Prostate Gland With Or Without Otis Urethrotomy Before Surgery – A Single Institution Experience - Shrestha, Naresh Man (Journal of Nepalgunj Medical College, 2017)
Background: Transurethral resection of prostate (TURP) is considered as the gold standard surgical treatment for Benign prostatic Hyperplasia (BPH). Among many post TURP complications, urethral stricture is one of the most dreaded urological complications, which may result in lifelong misery. The present study aimed to report the outcomes of Otis urethrotomy to prevent urethral stricture before TURP.Method: This was a comparative study between two equal groups of 100 patients who met inclusion criteria. Study conducted in the department of surgery, Urology unit, Nepalgunj Medical College from 2014 May to 2016 April. In group A, included all the patients underwent TURP without Otis urethrotomy and in group B , included all patients underwent TURP after doing Otis Urethrotomy. The patients were evaluated for evidence of urethral stricture formation.Result: In Group A, 20 patients out of 100(20%) developed urethral stricture whereas in Group B, 8 patients out of 100(8%) developed urethral stricture .The rate of Urethral Stricture in Group A is significantly more than in Group B (p